1978
DOI: 10.1042/bj1740485
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of UDP-glucuronosyltransferase as indicated by its differential development and inducibility by glucocorticoids. Demonstration of two groups within the enzyme's activity towards twelve substrates

Abstract: 1. UDP-glucuronosyltransferase activity towards 12 substrates has been assessed in rat liver during the perinatal period. 2. Between days 16 and 20 of gestation, enzyme activities towards the substrates 2-aminophenol, 2-aminobenzoate, 4-nitrophenol, 1-naphthol, 4-methylumbelliferone and 5-hydroxytryptamine (the 'late foetal' group) surge to reach adult values, while activities towards bilirubin, testosterone, beta-oestradiol, morphine, phenolphthalein, and chloramphenicol (the 'neonatal' group) remain negligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(64 citation statements)
references
References 22 publications
4
59
1
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Early studies suggested that 'late fetal and neonatal clusters' of inducible rat hepatic UGT activities [74] were identical to aryl hydrocarbon-and phenobarbital-inducible UGT activities, respectively [15,16]. Induction of UGTs from low fetal UGT activities to perinatal and adult values has been reviewed [56].…”
Section: Page 9 Of 31mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Early studies suggested that 'late fetal and neonatal clusters' of inducible rat hepatic UGT activities [74] were identical to aryl hydrocarbon-and phenobarbital-inducible UGT activities, respectively [15,16]. Induction of UGTs from low fetal UGT activities to perinatal and adult values has been reviewed [56].…”
Section: Page 9 Of 31mentioning
confidence: 99%
“…Two groups from the United Kingdom (Wishart 1978;Dutton & Leakey 1981;Leakey et al 1983;Coughtrie et al 1988;Scragg et al 1983Scragg et al & 1985 have performed extensive investigation of the development of hepatic UGT activity in the rat. They have demonstrated that three distinct developmental clusters of UGT activity exist.…”
Section: Glucuronidation By the Neonatal Rat Livermentioning
confidence: 99%
“…These developmental clusters are termed ''late foetal'', ''neonatal'' and ''postweaning''. The ''late foetal'' cluster of UGTs (possibly mainly UGT1 isoforms) metabolises the planar phenolic compounds (para-nitrophenol, 2-aminophenol and 1-naphthol) and develops immediately prior to birth, surging to maximal levels (above adult levels) within days before declining (Wishart 1978). Activity falls away in early infancy reaching a minimum at 13-16 days (Scragg et al 1983) before surging again to a second peak at 30-40 days.…”
Section: Glucuronidation By the Neonatal Rat Livermentioning
confidence: 99%
See 2 more Smart Citations